Constraining Elementary Teachers' Work:Dilemmas and Paradoxes Created by State Mandated Testing - Sandra Mathison; Melissa Freeman (Arizona State University, 2003)
There are frequent reports of the challenges to teacher professionalism associated with high stakes and mandated testing (McNeil, 2000). So, we were not surprised in this year-long study of two elementary schools in upstate New York to hear teachers talk about the many ways the 4th grade tests in English Language Arts, Mathematics and Science undermine their ability to do their jobs with integrity. We came to understand in more nuanced ways the ongoing tension created by teachers' desires to be professionals, to act with integrity, and at the same time to give every child a chance to succeed. What we found in these schools is that the high stakes tests continually forced teachers to act in ways they did not think were professional and often resulted in creating instructional environments that teachers did not think were conducive to student success. The teachers at these elementary schools are not radicals. They do not seek complete autonomy, they do not eschew the need for accountability (even bureaucratic accountability), they find some virtue in state mandated tests, they are content within centralized systems that proscribe some aspects of their work. But, they also perceive themselves as professionals with both the responsibility and capability of doing their jobs well and in the best interests of their students. New York State's outcomes based bureaucratic accountability system tests their resolve, makes them angry or frustrated, and requires unnecessary compromises in their work.